2011
DOI: 10.1017/s1751731111000085
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of the novel compounds creatine and pyruvateon lipid and protein metabolism in broiler chickens

Abstract: The effects of pyruvate (Pyr), creatine pyruvate (Cr-Pyr) and creatine (Cr) on lipid and protein metabolism were compared in broiler chickens. A total of 400 1-day-old male birds (Aconred) were allocated to four groups, each of which included four replicates (25 birds per replicate). Treatments consisted of unsupplemented basal diet (Control), basal diet containing 2% Pyr, basal diet containing 3% Cr and basal diet containing 5% Cr-Pyr. Cr-Pyr and Pyr significantly decreased the hepatic triglyceride and serum … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
30
0
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(38 citation statements)
references
References 42 publications
7
30
0
1
Order By: Relevance
“…The abdominal fat tissue grows faster compared with other fat tissues (Butterwith, 1989) and it reaches its maximum rate of growth at 42 days of age (Havenstein et al, 2003). It is the key indicator used to judge total body fat (Chen et al, 2011) because it is linked directly to the total body fat content in broiler chickens (Sonaiya, 1985). Our results agreed with previous studies of broiler chickens, pigs and White Pekin ducks (Corzo et al, 2003;Tan et al, 2009;Wu et al, 2011).…”
Section: Resultssupporting
confidence: 90%
See 2 more Smart Citations
“…The abdominal fat tissue grows faster compared with other fat tissues (Butterwith, 1989) and it reaches its maximum rate of growth at 42 days of age (Havenstein et al, 2003). It is the key indicator used to judge total body fat (Chen et al, 2011) because it is linked directly to the total body fat content in broiler chickens (Sonaiya, 1985). Our results agreed with previous studies of broiler chickens, pigs and White Pekin ducks (Corzo et al, 2003;Tan et al, 2009;Wu et al, 2011).…”
Section: Resultssupporting
confidence: 90%
“…The levels of plasma triglyceride (TG), total cholesterol (TC), high-density lipoprotein cholesterol (HDL-C), lowdensity lipoprotein cholesterol (LDL-C) and nonesterified fatty acids (NEFA) were estimated spectrophotometrically using commercial diagnostic kits (Jiancheng Bioengineering Institute, Nanjing, China; Chen et al, 2011). Each sample was analyzed in triplicate.…”
Section: Assay Of Lipid Parametersmentioning
confidence: 99%
See 1 more Smart Citation
“…The present study showed that transportation or CMH supplementation had no effect on dressing percentage, breast and thigh muscle yield, and abdominal fat of broilers, which is in accordance with some previous studies (Bianchi et al, 2005;Doctor and Poltowicz, 2009;Chen et al, 2011). Dadgar et al (2010) found that birdsexperienced a 3-to 4-h transport under higher temperature (20 < T ⩽ 30°C) showed a lower pHu and higher cooking loss in breast muscle than those transported under lower temperature (T⩽20°C).…”
Section: Creatine Monohydrate In Transported Broilerssupporting
confidence: 92%
“…Creatine plays a critical role in energy metabolism, and it is the only organic compound that is involved in protein metabolism and that participates in the muscular energy buffering system (Khajali & Wideman, 2010;Chen et al, 2011). Michiels et al (2012) reported that a diet supplemented with GAA (0.6 and 1.2 g/kg) markedly increased the creatine concentration in broiler breast meat.…”
Section: Effects Of Guanidionoacetic Acid and Arginine Supplementatiomentioning
confidence: 99%